Reversed triads - Marin Dinu (Theoretical and Applied Economics, 2014)

(untitled)
The upward trend suggested by the conceptualization of desires generates, paradoxically, the lower rung material precariousness. Meanwhile, the materialization of desires is possible, in an equally paradoxical way, only through the inflation of beliefs.